Efektivitas Pembukaan Rekening Secara Online Melalui Layanan Digital Saving Pada Bank BRI Kantor Kas Chevron Rumbai - Rahmadani, Lesty; Azmi, Zul (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study aims to find out how effective account opening is, the obstacles experienced, the mechanism for opening an account, and the advantages that customers get when using digital saving services. The location of the research was conducted at the Chevron Rumbai Cash Office. This kind of research uses a descriptive methodology and is qualitative. Primary data and secondary data were the sources of the data used in this study. The data analysis tool used in this study is NVivo 12. The results of this study are (1) Account opening through digital saving services at BRI Chevron Cash Office has been effective, (2) The obstacles that usually occur when using digital saving service can come from internal and external factors, ( 3) The mechanism for opening an account through digital saving services at BRI's Chevron Cash Office is considered to be in accordance with the established procedures determined by the company, (4) Customers who use digital saving services when opening an account will get the advantage that customers are automatically registered as BRI Mobile Banking (BRIMo) users, BRI Bank KK Chevron Rumbai has successfully implemented Electronic Service Quality (E-Service Quality).